Esophageal morphometric and biomechanical changes during aging in rats. Issue 11 (25th August 2015) - Zhao, J.; Gregersen, H.
Abstract Background Human studies have demonstrated aging‐related changes in esophagus which may contribute to the increased rate of gastro‐esophageal reflux in elderly. The aim of this study was to investigate esophageal morphometric and biomechanical remodeling in aging rats to obtain detailed information about aging‐related changes. Methods Twenty‐four male Wistar rats, aged from 6 to 22 months, were studied. Morphometric data were obtained by measuring the wall thickness and cross‐sectional area. The esophageal diameter and length were obtained from digitized images of the segments at preselected luminal pressure levels and at no‐load and zero‐stress states. Circumferential and longitudinal stresses (force per area) and strains (deformation) were computed from the length, diameter and pressure data, and from the zero‐stress state geometry. Key Results The esophageal parameters such as the weight per unit length, the wall thickness and the wall cross‐sectional area increased slightly from 6 to 22 months (p < 0.05 to p < 0.001). The opening angle gradually decreased during aging (p < 0.05). The interface between the mucosa–submucosa and muscle layers slightly moved outwards and the neutral axis moved inwards during aging. The stress–strain data showed that the esophageal wall became stiffer circumferentially and longitudinally during aging (p < 0.05, p < 0.01). However, the circumferential wall stiffness showed no further change after 12 months. Conclusions & Inferences A pronounced morphometric and biomechanical remodeling occurred in the rat esophagus during aging.